Pengaruh Environmental, Social, Governance (ESG) Risk terhadap Kinerja Keuangan Perusahaan: Studi Empiris pada Perusahaan yang terdaftar di Bursa Efek Indonesia Tahun 2023 - Lestari, Gita; Pebriyani, Dewi (Universitas Negeri Padang, 2025)
The purpose of this study is to analyze the effect of environmental, social, governance and intellectual capital on corporate financial performance in companies listed on the Indonesia Stock Exchange. The research uses a quantitative approach with a causal associative method. The sampling technique consisted of 65 companies that met the criteria. The data used is secondary data, including ESG Risk scores from Morningstar Sustainalytics and financial data obtained from the official website of the Indonesian Stock Exchange. The company's financial performance is measured using Return on Assets (ROA). The research results show that ESG Risk has a negative effect on the financial performance of companies listed on the Indonesia Stock Exchange which is measured using ROA. This means that a high level of ESG Risk can reduce the company's financial performance.